Extracellular enzyme stoichiometry reveals carbon and nitrogen limitations closely linked to bacterial communities in China’s largest saline lake - Zhang, Weizhen; Liu, Yongqin; Geng, Mengdie; Chen, Ruirui; Wang, Jiyi; Xue, Bin; Xie, Ping; Wang, Jianjun (Frontiers in Microbiology, 2022)
Saline lakes possess substantial carbon storage and play essential roles in global carbon cycling. Benthic microorganisms mine and decompose sediment organic matter via extracellular enzymes to acquire limiting nutrients and thus meet their element budgets, which ultimately causes variations in sediment carbon storage. However, current knowledge about microbial nutrient limitation and the associated organic carbon changes especially in saline lake remains elusive. Therefore, we took Qinghai Lake, the largest saline lake of China, as an example to identify the patterns and drivers of microbial metabolic limitations quantified by the vector analyses of extracellular enzyme stoichiometry. Benthic microorganisms were dominantly colimited by carbon (C) and nitrogen (N). Such microbial C limitation was aggravated upon the increases in water salinity and sediment total phosphorus, which suggests that sediment C loss would be elevated when the lake water is concentrated (increasing salinity) and phosphorus becomes enriched under climate change and nutrient pollution, respectively. Microbial N limitation was predominantly intensified by water total nitrogen and inhibited by C limitation. Among the microbial drivers of extracellular enzyme investments, bacterial community structure consistently exerted significant effects on the C, N and P cycles and microbial C and N limitations, while fungi only altered the P cycle through species richness. These findings advance our knowledge of microbial metabolic limitation in saline lakes, which will provide insights towards a better understanding of global sediment C storage dynamics under climate warming and intensified human activity.